THE EFFECTS OF TEACHING TECHNIQUE AND LANGUAGE ATTITUDES TOWARDS STUDENTS’ SPEAKING SKILL AT SENIOR HIGH SCHOOLS IN PURWAKARTA WEST JAVA - Occe Luciana (Jurnal Ilmu dan Budaya, 2016)
The purpose of this study was to determine the effect of teaching technique and language attitude towards students’ speaking skill. The research was conducted through the technique of experiment with a sample size of 96 people in a cluster sampling consisting of two states school students are among 58 students of SMAN 2 Purwakarta, and 58 students of SMAN 3 Purwakarta. Both of them are in class XI. Then they were divided into four groups. The data was collected by carrying out the test results speaking skills for measuring speaking skill and the provision of a questionnaire data were collected and processes through the rules of descriptive statistics and inferential analysis with 2 pathways ANOVA. From the analysis concluded there is a significant effect of teaching technique towards students’ speaking skill. That is proved by value of F0 = 21.324 and Sig. = 0.000 < 0.05. In other words, the average speaking skill of students who are taught by using role-play technique and conventional has significant differences. But there is no significant effect of attitude towards languagespeaking skill. That is proved by the value of F0 = 0.724 and Sig. = 0.397 > 0.05. It means that the difference (Mean) of respondents who have a high attitude with students who have low language attitude is not a significant difference. And there is no significant effect between teaching technique and language attitude towards language speaking skill. That is proved by the value of F0 = 2.894 and Sig. = 0.092 > 0.05